Spatio-temporal prevalence of porcine cysticercosis in Madagascar based on meat inspection - Porphyre, Vincent (Parasit Vectors, 2015)
BACKGROUND: Taenia solium cysticercosis is a parasitic meat-borne disease that is highly prevalent in pigs and humans in Africa, but the burden is vastly underestimated due to the lack of official control along the pork commodity chain, which hampers long-term control policies. METHODS: The apparent and corrected prevalences of T. solium cysticercosis were investigated in pork carcasses slaughtered and retailed in Antananarivo (Madagascar), thanks to a 12-month monitoring plan in two urban abattoirs. RESULTS: Overall apparent prevalence was estimated at 4.6 % [4.2 – 5.0 %]. The corrected overall prevalence defined as the estimated prevalence after accounting for the sensitivity of meat inspection was 21.03 % [19.18- 22.87 %]. Significant differences among geoclimatic regions were observed only for indigenous pigs, with an apparent prevalence estimated at 7.9 % [6.0 – 9.9 %] in the northern and western regions, 7.3 % [6.0 – 8.6 %] in the central region, and 6.2 % [4.7 – 7.8 %] in the southern region. In the central region, where both exotic and indigenous pigs were surveyed, indigenous pigs were 8.5 times [6.7 – 10.7] more likely to be infected than exotic improved pigs. Urban consumers were more likely to encounter cysticercosis in pork in the rainy season, which is a major at risk period, in particular in December. Differences between abattoirs were also identified. CONCLUSION: Our results underline the need for improved surveillance and control programmes to limit T. solium cysticercosis in carcasses by introducing a risk-based meat inspection procedure that accounts for the origin and breed of the pigs, and the season.